A Study of the Development of the Concept of Social Justice in the Social Encyclicals 1891-1991 - Perera, W.V.K.P. (International Postgraduate Research Conference 2019, Faculty of Graduate Studies, University of Kelaniya, Sri Lanka, 2019)
In an inquiry into the social dimension of justice, what is noticed in the Social Encyclicals which appeared since 1891 onwards is the traditional Aristotelico-Thomistic concepts of Distributive and Commutative Justice as well as Luigi Taparelli D’ Azaegllio’s neo-Thomistic notion of Social Justice. The main focus of the present research is the development of the concept of Social Justice in the Catholic Social Encyclicals. The period envisaged stretches from the issuance of Leo XIII’s Rerum Novarum (1891) to that of John Paul II’s Centesimus Annus which commemorated the former’s centenary in 1991; the social encyclicals of this period are analyzed according to the method of literary criticism. Though David Hollenbach and Charles E. Curran mentions only the occurrences of various forms of Justice in the encyclicals, they have not traced the development of the concept of Social Justice in an elaborated detailed study. Neither has anyone else made a study of Social Justice in the encyclicals nor employed the technique of literary criticism. Hence this research fills in that twofold lacuna.
Keywords: Social Encyclicals; Thomas Aquinas; Neo-Thomism; Luigi Taparelli D’ Azaegllio; Social Justice